OsAPSE modulates non-covalent interactions between arabinogalactan protein O-glycans and pectin in rice cell walls - De Coninck, Tibo; Verbeke, Isabel; Rougé, Pierre; Desmet, Tom; Van Damme, Els J. M. (Frontiers in Plant Science, 2025)
Flexibility of cell walls is crucial to accommodate cell elongation and growth, typically associated with the reorganization of cell wall polysaccharides. Seed germination is a fast-paced developmental process in which cell wall adaptability is highly required. The plant cell utilizes multiple strategies to obtain a flexible cell wall and in part relies on cell wall-active enzymes to loosen both covalent and non-covalent interactions between cell wall polysaccharides. OsAPSE is an example of a cell wall-active enzyme originating from Japanese rice (Oryza sativa subsp. Japonica) belonging to the glycoside hydrolase family 27 (GH27), potentially active on the pectin–arabinogalactan protein O-glycan junction. We provide insights into the biochemical and enzymatic properties of this protein, characterized by the presence of a GH27 domain linked to a ricin-B-like domain. Using small-scale production experiments in a cell-free protein synthesis system, we demonstrated the catalytic activity of the recombinant OsAPSE towards synthetic and natural substrates. Furthermore, subcellular localization analysis and in silico data suggest that OsAPSE may undergo unconventional secretion to the cell surface. We hypothesize that OsAPSE plays a role during rice seed germination by removing terminal α-D-Galp and β-L-Arap moieties along the pectin–arabinogalactan protein O-glycan network. This activity may abolish non-covalent interactions between pectic rhamnogalacturonan I and O-glycans of arabinogalactan proteins, contributing to cell wall relaxation for growth during germination.